2022
DOI: 10.1002/app.53076
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of cellulose nanofibers/α‐zirconium phosphate nanosheets composite polyvinyl alcohol ion‐conductive organohydrogel and its application in strain sensors

Abstract: The poor mechanical and electrical properties and single function of conventional conductive hydrogels severely limit their application in flexible sensors. Here, a multifunctional nanomaterial composite high-strength hydrogel strain sensor was prepared by incorporating α-zirconium phosphate (α-ZrP) nanosheets with hydroxyl functional groups on the surface and cellulose nanofibers (CNFs) into a poly(vinyl alcohol) (PVA)matrix simultaneously, using a binary glycerol/water solution as the dispersion medium and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Poly (vinyl alcohol) PVA, is a water-soluble polymer with unique characteristics, including high tensile strength and biocompatibility and also PVA-borax hydrogel has been widely recognized for its excellent properties in terms of mechanical strength, stretchability, and biocompatibility using borax as a crosslinking. However, it is well known that PVA borax hydrogels have poor elasticity and tensile strength and no current transfer (7,9). To solve this challenge, many studies on the use of other materials, such as graphene, cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs), and MXene (Ti 3 C 2 ), have been included in PVA-based hydrogels (23).…”
Section: Resultsmentioning
confidence: 99%
“…Poly (vinyl alcohol) PVA, is a water-soluble polymer with unique characteristics, including high tensile strength and biocompatibility and also PVA-borax hydrogel has been widely recognized for its excellent properties in terms of mechanical strength, stretchability, and biocompatibility using borax as a crosslinking. However, it is well known that PVA borax hydrogels have poor elasticity and tensile strength and no current transfer (7,9). To solve this challenge, many studies on the use of other materials, such as graphene, cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs), and MXene (Ti 3 C 2 ), have been included in PVA-based hydrogels (23).…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated inFig.1 (a), the FTIR spectra of ZnO/PVA/CHI composite were recorded from 4000 to 400 cm -1 .The absorption peak around 3415 cm -1 in the spectrum belongs to the stretching vibrations of surface O-H bonds from PVA and N-H bonds from CHI [21][22] .The bands located at 2926,1421, and 1116cm -1 are respectively put down to the aliphatic C-H stretching vibration, the CH-OH stretching vibration, and the -CH 2 stretching vibration in the PVA [22][23] .The stretching vibration absorption peak appeared at 1635 cm -1 in the spectra can be attributed to the O-H bond in the CHI. Among the peak assigned to ZnO, the peak located at 437 cm -1 is attributed to the O-Zn stretching vibrations on Zn atoms [24] .…”
Section: Resultsmentioning
confidence: 99%
“…[6] Liu et al demonstrated that a similar PVA-glycerol-NaCl hydrogel maintained 86% transparency even with the addition of zirconium phosphate nanosheets and cellulose nanofibers (CNFs). [10] Another PVA-glycerol-sodium alginate (SA)-CaCl 2 system developed by X. Liu et al achieved 96% transparency. [17] Though incorporation of polyols is beneficial for transparency, their effects on the sensing performance of ion-conductive PVA systems have not been sufficiently studied, highlighting the need for further research in this area.…”
Section: Microstructure Shows Amorphousness After Addition Of Zn Salt...mentioning
confidence: 99%
“…Flexible moieties or dynamic bonds are commonly employed for softness, while hierarchical morphologies, crosslinked double networks, or structural nanomaterials such as CNFs are often used to maintain mechanical strength. [10,11,14,16] X. Liu et al's PVA-glycerol-SA-CaCl 2 network consists of dynamic hydrogen and ion-ligand bonds capable of dissipating energy. [17] Y. Liu et al reported a soft-hard network gel that uses PVA and poly(vinyl pyrrolidone) as the soft, flexible portions while cellulose nanocrystal (CNC)-Fe 3+ complexes serve as the hard, tough crosslinkers.…”
Section: Mechanical and Adhesive Properties Of Organohydrogel Correla...mentioning
confidence: 99%
See 1 more Smart Citation